x/11=x/11-1

Simple and best practice solution for x/11=x/11-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x/11=x/11-1 equation:



x/11=x/11-1
We move all terms to the left:
x/11-(x/11-1)=0
We get rid of parentheses
x/11-x/11+1=0
We multiply all the terms by the denominator
x-x+1*11=0
We add all the numbers together, and all the variables
11!=0
There is no solution for this equation

See similar equations:

| -3x=4=1 | | ^15k=15 | | 7n/6=5/3 | | 10=3(x-1)-(x-9) | | 12/100=2/x | | 2h+138=1,040 | | 138+2h=1,040 | | 138+2h=1.040 | | 4x-4=9x+17 | | -7(5-3n)=-140 | | 1/2x+2/3x+12=18 | | 23229=34x/1-(1+34)^-34 | | 7(d-5)=12=15 | | 36=4×r | | -3(1-7n)=123 | | Z+4-6=10-2z | | 4+-n=-15 | | 8m=172 | | 16^(-x+44)=128 | | 174=48n+18 | | 3(7k^2+5k-2)=0 | | 3(7k+5k-2)=0 | | 7x-5=212 | | 7(n+8)-n=86 | | 13x+50=9x+100 | | 8z=11 | | 5h−7=1+h | | 3(7k^2+5k-6)=0 | | 7x+3x+11+39=180 | | 3(3-3x)=2(X+3)+30 | | 3(7k+5k-6)=0 | | C^2-13^c+42=0 |

Equations solver categories